The adult learner : the definitive classic in adult education and human resource development - Knowles, Malcolm S. 1913-1997; Holton, Elwood F., 1975-; Robinson, Petra A.; Caraccioli, Corina (Routledge, Taylor & Francis Group, 2025)
"How do you tailor education to the learning needs of adults? Do they learn differently from children? How does their life experience inform their learning processes? These were the questions at the heart of Malcolm Knowles' pioneering theory of andragogy which transformed education theory in the 1970s. The resulting principles of a self-directed, experiential, problem-centred approach to learning have been hugely influential and are still the basis of the learning practices we use today. Understanding these principles is the cornerstone of increasing motivation and enabling adult learners to achieve. The 10th edition of The Adult Learner has been revised to include: The two chapters on diversity, inclusion and belonging in adult learning, and andragogy and the online adult learner have been greatly expanded to reflect the importance of these topics to the field today. The accompanying Instructor and Student Resources website provides free digital materials designed to enhance student learning and save instructors time when preparing lessons. Resources include: Ready-to-use PowerPoint slides to save instructor time when planning lessons Learning objectives and part outlines for structured learning Suggested class discussions, exercises, and scenario-based activities Downloadable instruments for chapters 19 to 22 Video explaining the Andragogy In Practice model A chapter-by-chapter Instructor Manual and a corresponding Student Guide to enhance learning outcomes. If you are a researcher, practitioner, or student in education, an adult learning practitioner, training manager, or involved in human resource development, this is the definitive book in adult learning you should not be without"--